Morphologically high‐grade trichoblastic carcinoma: a clinicopathological study with long‐term clinical follow‐up. Issue 7 (6th April 2021) - Mehta, Arjun; Davey, Jonathan; Wiedemeyer, Katharina; Brenn, Thomas
Abstract : Aims: Trichoblastic carcinomas (malignant trichoblastomas) are rare and poorly documented neoplasms characterised by malignant transformation of a pre‐existing benign trichoblastoma, and are subdivided histologically into low‐grade and high‐grade tumours. Whereas morphologically low‐grade trichoblastic carcinomas show indolent behaviour, morphologically high‐grade trichoblastic carcinomas have been associated with a poor prognosis, but little is known about their true biological potential. The aim of this study was to better define the clinicopathological features and outcomes of morphologically high‐grade trichoblastic carcinomas. Methods and results: Four high‐grade trichoblastic carcinomas were retrieved from departmental files, and the clinical and histopathological features and follow‐up were recorded. The tumours presented as nodules on the scalps, necks and shoulders of adults (median age, 40 years; range, 30–55 years) with a female predominance of 3:1. Three patients had a longstanding history with recent change. Histologically, three tumours were characterised by an expansile cellular nodule composed of sheets of pleomorphic epithelioid cells with brisk mitotic activity and necrosis arising in a background of a benign trichoblastoma. One tumour showed a more gradual transition from a benign trichoepithelioma to an undifferentiated carcinoma with infiltrative growth and perineural infiltration. All patients were alive with no evidence of recurrence or metastasis following complete excision after a median follow‐up of 96 months (range, 30–180 months). Conclusions: The correct diagnosis of high‐grade trichoblastic carcinoma relies on adequate sampling and recognition of the benign trichoblastic precursor lesion, i.e. trichoblastoma or trichoepithelioma. Despite the concerning histological features of the malignant component, the tumours appear to be less aggressive than previously thought. Abstract :